Age Gender and Site Effect on Immunohistochemical Expression of TGF-β1 and IFN-γ in Hereditary Gingival Fibromatosis - Ali Omran Mousa (Journal of Global Pharma Technology, 2019)
Back ground: Gingiva as other part of oral cavity has been effected with hereditary diseases. When navigate in the jungle of gingival disease hereditary gingival fibromatosis will appeared as vague hereditary condition and the pathogeneses of disease is not clearly understood. Clinically it’s characterized by massively increasing in gingival tissue mass, which appeared more fibrous. Transforming growth factor beta 1 (TGF-β1) is growth factor which had critical role in pathogeneses of (HGF) together with interferon gama (IFN-γ) which inflammatory cytokines the level of these cytokines may be changed according to gender, age or site distribution (generalized, localized). Aim: To evaluate the level of TGF-β1and IFN-γ immunohistochemically in hereditary gingival fibromatosis according gender, age and site distribution. Methods: Immunohistochemistry for detection of TFG-β1 and IFN-γ in paraffin embedded tissue sections for 17 blocks of hereditary gingival fibromatosis. Result: Non-significant difference of TGF-β1 according to gender, age and site in .Also Non- significant difference of INF -γ according to gender and site. On other hand significant difference of INF-γ according to age. Conclusion: Age, gender and site have no effect on expression of TGF-β1 in hereditary gingival fibromatosis; same findings were for IFN-γ except the age which has an obvious effect on IFN-γ expression.Keywords: Hereditary Gingival Fibromatosis.